Understanding conflict among experts working on controversial species: A case study on the Australian dingo. Issue 3 (10th February 2023) - Donfrancesco, Valerio; Allen, Benjamin L.; Appleby, Rob; Behrendorff, Linda; Conroy, Gabriel; Crowther, Mathew S.; Dickman, Christopher R.; Doherty, Tim; Fancourt, Bronwyn A.; Gordon, Christopher E.; Jackson, Stephen M.; Johnson, Chris N.; et al.
Abstract: Expert elicitation can be valuable for informing decision‐makers on conservation and wildlife management issues. To date, studies eliciting expert opinions have primarily focused on identifying and building consensus on key issues. Nonetheless, there are drawbacks of a strict focus on consensus, and it is important to understand and emphasize dissent, too. This study adopts a dissensus‐based Delphi to understand conflict among dingo experts. Twenty‐eight experts participated in three rounds of investigation. We highlight disagreement on most of the issues explored. In particular, we find that disagreement is underpinned by what we call "conflict over values" and "conflict over evidence." We also note the broader role played by distrust in influencing such conflicts. Understanding and recognizing the different elements shaping disagreement is critical for informing and improving decision‐making and can also enable critique of dominant paradigms in current practices. We encourage greater reflexivity and open deliberation on these aspects and hope our study will inform similar investigations in other contexts. Abstract : This study entails a social investigation into why experts may disagree about conservation and wildlife management issues, stressing the importance of understanding and emphasizing dissent in current practices. In particular, we outline "conflict over values" and "conflict over evidence" as two aspects shaping experts' disagreement, and discuss the role of distrust in influencing such conflicts.